2021
DOI: 10.1038/s41586-021-03525-z
|View full text |Cite
|
Sign up to set email alerts
|

NOTUM from Apc-mutant cells biases clonal competition to initiate cancer

Abstract: The APC tumour suppressor gene is the most commonly mutated gene in colorectal cancer (CRC). Loss of Apc in intestinal stem cells (ISCs) drives aberrant Wnt signalling and adenoma formation in mice 1 . We previously showed that a reduction in WNT-ligand secretion increases the ability of Apc-mutant ISCs to colonise a crypt (fixation) and accelerate tumourigenesis 2 . Here, we investigate key mechanistic processes whereby Apc-mutant cells gain a clonal advantage over wild-type counterparts to achieve fixation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
145
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 169 publications
(167 citation statements)
references
References 35 publications
6
145
0
Order By: Relevance
“… 29 , 30 More recently, Notum has been identified as a key mediator for adenomatous polyposis coli (Apc)-mutated tumor cell fixation and tumor formation, while Notum inhibitors abrogate the ability of Apc-mutant cells to expand. 31 These pieces of evidence highlight the importance of Notum as a novel target for drug discovery.…”
Section: Introductionmentioning
confidence: 99%
“… 29 , 30 More recently, Notum has been identified as a key mediator for adenomatous polyposis coli (Apc)-mutated tumor cell fixation and tumor formation, while Notum inhibitors abrogate the ability of Apc-mutant cells to expand. 31 These pieces of evidence highlight the importance of Notum as a novel target for drug discovery.…”
Section: Introductionmentioning
confidence: 99%
“…Although Apc- mutant adenomas are independent of Wnt ligands ( 15 , 58 ), we found that several Wnt antagonists were decreased after Apc ; Lef1 deletion. This observation may be functionally significant, as a recent study showed that the secreted Wnt antagonist Notum produced by the Apc -mutant adenomas inhibits Wnt signaling in the neighboring WT ISCs ( 59 , 60 ). We found that LEF1 expression was restricted to ligand-independent CRCs, whereas it was not expressed in the ligand-dependent CRCs.…”
Section: Discussionmentioning
confidence: 95%
“…In this frame, two studies recently described the capability of Apc-mutated adenoma cells to inhibit stem cell activity of non-mutated cells within the same crypt and adjacent crypts through secretion of soluble Wnt antagonists [ 107 ]. Among these factors, a prominent role is played by NOTUM, whose pharmacological inhibition blocks adenoma formation [ 28 ]. Other important information has been provided by an innovative tracking system, the Confetti-derived Red2Onco, by which oncogenes such as mutated KRAS or PI3K are inserted only in RFP+ tumor cells.…”
Section: Merging Methodologies and Evolving Concepts: Ccsc Plasticity And The Nichementioning
confidence: 99%
“… The timetable of landmark studies that have contributed to defining cCSC biological features and functions. Numbers in parentheses indicate references [ 5 , 6 , 9 , 12 , 17 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. …”
Section: Figurementioning
confidence: 99%